Intellectual property : patents, copyright, trade marks and allied rights - Cornish, W.R. (Sweet & Maxwell LondonGB, 1996)
Provides comprehensive and authoritative coverage of the whole spectrum of intellectual property law as it applies in the United Kingdom. Discusses the GATT Agreement on trade-related aspects of intellectual property rights (TRIPS).